Exploring the Lived Experiences of Mothers of Children with Intellectual Disability: A Phenomenological Approach - Ahmad Sharifi Ardani; Ahmad Yarmohammadian; Amir Ghamrani (Kerman University of Medical Sciences, 2022)
Introduction: Living with an intellectually disabled child in the family is associated with some concerns and challenges. However, mothers who play the traditional role of "caregiver" have to take on more responsibilities for their intellectually disabled children. Thus, they face more pressures and psychological problems and experiences. To this end, this study aimed to explore the lived experiences of mothers of children with intellectual disabilities.Methods: This qualitative study was conducted using a phenomenological approach. The participants were 12 mothers of children with intellectual disabilities who were selected using purposive sampling. The data were collected through in-depth interviews with the participants. The interviews were recorded, transcribed, and analyzed using Colaizzi's method of data analysis.Results: Analysis of the experiences of the mothers of children with intellectual disabilities revealed 7 main themes (blame, concerns about the future, child behavioral problems, disrupted interactions, stigma and social isolation, negative thoughts and feelings, and positive achievements) and 16 subthemes that were coded into subcategories of the main themes.Conclusion: The findings of this study can provide valuable insights into the severity of problems faced by mothers with intellectually disabled children and contribute to adopting supportive treatment strategies for these mothers and improving their mental health. These data can make professionals working with intellectually disabled children familiar with the main challenges and concerns and pave the way for psychologists and psychiatrists to design effective interventions based on the experiences of mothers and the cultural norms of the Iranian community.